SYSTEMATICS LITERATURE REVIEW: EKSPLORASI ETNOMATEMATIKA PADA AKTIVITAS MASYARAKAT - Wahyudi Wahyudi; Aan Putra (LPPM Universitas Bina Bangsa, 2022)
Ethnomathematics is mathematics that grows, develops and is practiced by cultural groups such as urban and rural communities, children of certain age groups, labor groups, indigenous peoples, and others. Ethnomathematics that links culture, one of which is community activity and mathematical concepts, certainly has mutually supportive characteristics. This paper discusses the review of results from several journals to obtain information on the application of ethnomathematics to community activities. This article aims to examine the concept of ethnomathematics in community activities by looking at reviews of results from several previous journals. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research on the topic area of an interesting phenomenon with certain relevant research questions. By using the SLR method, a systematic review and identification of journals can be carried out, each of which follows the established stages. Data collection was carried out by collecting and reviewing articles on ethnomathematics in community activities published in the 2015-2021 timeframe. There are 14 journal articles or proceedings used in this study which were obtained from the Publish or Perish and Googel Scholar applications. The results of this study are the existence of ethnomathematics in community activities where mathematical concepts are contained in every job and community activity